Bezpieczeństwo a kształtowanie przestrzeni - Mordwa, Stanisław (Space – Society – Economy, 2009)
In this chapter author presents the most important theories on creating safe space. The most influential of them were detailed examined i.e. Newmana, Jeffry, Jacobs, Van Soomeren, Clarke, Nelsona and Brantinghams’ theories. Next the Crime Prevention through Environmental Design program were discussed. In the last part of the chapter examples of program implementation were presented.